Effect of post-warm-up three different duration self-selected active rests on 100 meter swimming performance: preliminary findings - Türkmen, D.; Günay, E.; Güdücü, Ç.; Öniz, A.; Bediz, C. S. (Montenegrin Journal of Sports Science and Medicine, 2021)
The question of when the optimal effect of warm-up is reached after the warm-up phase in swimming compe- titions is still not fully elucidated. The purpose of this study was to see how self-selected active rest in three dif- ferent duration periods affected 100-m maximum swimming performance. Eight well-trained elite swimmers (6 males and 2 females, mean age: 17.2 ± 3, mean 616 FINA points) were included in the study. After the participants completed a standard warm-up consisting of dryland-based dynamic warm-up (10-min) and in-water warm-up protocols (1200-m / ~25-min) in 3 different sessions, they observed different transition phase periods (15, 30 and 45-min) with standard clothes in their maximum heart rate of 30% and self-selected movement forms (stretching, walking, etc.) completed by active rest. Subsequently, swimmers carried out the 100-m maximum time-trial swim test using their main stroke. Tympanic temperature (Ttympanic), forehead temperature (Tforehead), heart rate (HR), rating of perceived exertion (RPE), and maximal 100-m-time-trial (TT) were recorded during all sessions. Measurements were evaluated in repeated measures ANOVA. Delta calculation was used to score changes and strengthen the analysis. The 100-m time-trial demonstrated a trend of improvement in 30-min active rest (p=0.037). In addition, there was no difference between rest times in Tforehead, Ttympanic, HR, and RPE conditions (p>0.05). The 30-min active rest interval improved 100-m swimming performance by 1.6% and 0.8% compared to 15-min and 45-min active rest. The positive effect of pool warm-up can be maintained for up to 30 minutes with self-paced active rest.